Geological position and age of Tuxen-Rasmussen layered gabbroid intrusion (West Antarctica) - Mytrokhyn, O.V.; Bakhmutov, V.G.; Aleksieienko, A.G.; Gavryliv, L.I.; Mytrokhina, T.V. (Український антарктичний журнал, 2017)
Main objectives of the study were the identification of geological position of the TRGI and the clarification of its geological age. In addition to the field methods of the geological research the samples collected during this and the previous years were studied using optical and electron microscopy techniques in order to identify petrographic and mineralogical features of the gabbroids.